2016
DOI: 10.1016/j.addr.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of cancer therapeutics to extracellular and intracellular targets: Determinants, barriers, challenges and opportunities

Abstract: Advances in molecular medicine have led to identification of worthy cellular and molecular targets located in extracellular and intracellular compartments. Effectiveness of cancer therapeutics is limited in part by inadequate delivery and transport in tumor interstitium. Parts I and II of this report give an overview on the kinetic processes in delivering therapeutics to their intended targets, the transport barriers in tumor microenvironment and extracellular matrix (TME/ECM), and the experimental approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 254 publications
(285 reference statements)
0
95
0
Order By: Relevance
“…For the development of immune therapies against HGSOC, it is essential to understand the network of tumor microenvironment. If we could destroy the adipose tissue and the ECM around tumors, the accessibility of immune cells and other therapeutics might be increased and thus the therapy efficacy might be improved, an issue that has already drawn the attention of scientists (36).…”
Section: Discussionmentioning
confidence: 99%
“…For the development of immune therapies against HGSOC, it is essential to understand the network of tumor microenvironment. If we could destroy the adipose tissue and the ECM around tumors, the accessibility of immune cells and other therapeutics might be increased and thus the therapy efficacy might be improved, an issue that has already drawn the attention of scientists (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown that positively charged serum proteins are adsorbed on positively charged NPs, which often causes a shielding or protective effect on cell viability (Nafee et al, 2009;Schulze et al, 2009). These high-affinity proteins constitute the first layer of the biocorona, usually called the "hard corona" Tenzer et al, 2013;Au et al, 2016), and this corona basically determines the binding/internalization, as well as the following functionality of the NP. The significant cytotoxic effect of CS-IONPs can be explained by the high proteinabsorbing capacity of CS-coated surfaces, which might alter the conformation of absorbed proteins and lead to the disruption of physiological processes Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of genome‐editing proteins, such as Cas9, zinc finger nucleases, and recombinases, is particularly exciting as the “conditional” nature of their activity makes direct protein transduction a valuable alternative to integrating transgene technologies . However, intracellular protein transduction remains problematic due to poor membrane permeability, endosomal entrapment, and proteolytic degradation . Recent advances have delivered enzymes to the cytosol by nanoparticle assemblies, mechanical insertion through electroporation, microfluidic squeeze technology, or by achieving endosomal escape by membrane fusing .…”
Section: Introductionmentioning
confidence: 99%